The mythological manifestation in The Epistle of Forgiveness (Risalat al-Ghufran) by Abu al-ala al-Maʿarri - Hijara, Ali; Abbas, Haider (Al-Adab Journal, 2024)
Objectives:  This research aims to observe the mythological symbols that appear in the Epistle of Forgiveness ( Risalat al-Ghufran )  by Abu Al-Ala Al-Ma’arri, mentioning their effect on the journey of Ibn Al-Qarih ( the protagonist in Risalat al-Ghufran ) and how they were depicted and integrated according to the culture of the writer’s era, which is reflected in the work through the roots of ancient stories and their inherited events that It is transmitted from one generation to another into works of art.Methods: We followed the descriptive and analytical method based on the cultural context in revealing the similarities and resemblances of the characters and creatures, descriptions of places, and related mythical roots, without deviating from the comparative method, which is about revealing the extent to which Abu Alaa Al-Maarri was influenced by multiple cultures that struct his combinations between The product of this influence and what he wrote that belong to the Islamic culture of his time.Results: The research found that Abu Al-Ala Al-Maarri was influenced by mythological symbols derived from several myths to be based within the Epistle of Forgiveness ( Risalat al-Ghufran ), as narrative elements that formed the storytelling tools and events through Ibn al-Qarih's journey, which led The writer to introduce characters, places, and creatures with a structure similar to what was mentioned from narrative sources of ancient stories, whether that was consciously or influenced by collective memory, and the products of folklore.